Existence of Travelling Wave Solution of Nonlinear Equations with Nonlocal Advection (Journal of Partial Differential Equations, 1997)
In this paper, the existence of travelling wave solution for nonlinear equation wiili non local advection ρ\frac{∂}{∂t}(\frac{u^m}{m}) = \frac{∂²u}{∂x²}-\frac{∂}{∂x}[φ(k∗u)u]+u^nf(u) is studied in the case of m ≥ 1, n ≥ 1. When ε,φ, f, m and n satisfy some determinate conditions, there exists the travelling wave solution.